CHARACTERIZATION OF AA6061/ GRAPHITE COMPOSITES FOR ENHANCED MECHANICAL PROPERTIES USING MULTI-PASS FRICTION STIR PROCESSING - HAMZAH, MOHAMAD NASHRIQ (IRC, 2021)
The project studied the effects of number of passes on AA6061/Gr surface composites produced using a novel method of FSP with number of passes are defined as manipulated parameters varied at one, two, and three.